การวิเคราะห์และเปรียบเทียบลักษณะและเหตุผลของการเรียนเสริมของนักเรียนระดับปฐมวัยในกรุงเทพมหานคร : การวิจัยผสมวิธี - ดำริห์ ณัฐธิดา; ไตรวิจิตรคุณ ดวงกมล (An Online Journal of Education, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์คือ 1) เพื่อศึกษาลักษณะของการเรียนเสริมของนักเรียนระดับปฐมวัยในเขตกรุงเทพมหานคด้านวิชาที่เรียน จำนวนชั่วโมงที่เรียนเสริมต่อสัปดาห์ แบบการเรียนเสริม และค่าใช้จ่ายในการเรียนเสริมต่อเดือน 2) เพื่อศึกษาเหตุผลในการเรียนเสริม และไม่เรียนเสริมของนักเรียนระดับปฐมวัย 3) เพื่อเปรียบเทียบลักษณะของการเรียนเสริม และเหตุผลของการเรียนเสริมและไม่เรียนเสริมของนักเรียนระดับปฐมวัยที่มีภูมิหลังต่างกัน ดำเนินการวิจัยแบบผสมวิธี ประกอบด้วย 2 ระยะ คือ ระยะแรก ศึกษาข้อมูลเชิงคุณภาพ สัมภาษณ์ผู้ปกครองที่นักเรียนเรียนเสริม 15 คน และไม่เรียนเสริม 10 คน ระยะที่สองศึกษาข้อมูลเชิงปริมาณ โดยใช้แบบสอบถามจำนวน 594 ฉบับจากกลุ่มตัวอย่างผู้ปกครองนักเรียน 14 โรงเรียนทั้งโรงเรียนปกติและโรงเรียนมีชื่อเสียง วิเคราะห์ข้อมูลเชิงปริมาณด้วยสถิติบรรยาย การวิเคราะห์สถิติทดสอบ Pearson Chi-square และการวิเคราะห์ความแปรปรวนทางเดียว ผลการวิจัยที่สำคัญสรุปได้ดังนี้ 1) ลักษณะการเรียนเสริม นักเรียนระดับปฐมวัย ส่วนใหญ่เรียนเสริมทั้งด้านวิชาการและสันทนาการควบคู่กัน จำนวนชั่วโมงที่เรียนเสริมเฉลี่ยต่อคนต่อสัปดาห์ 6.57 ชั่วโมง ค่าใช้จ่ายในการเรียนเสริมเดือนละ 4117.56 บาท ส่วนมากเรียนเสริมเป็นกลุ่มใหญ่มากกว่า 5 คน และเรียนเสริมที่สถาบันสอนเสริม 2) ระดับเหตุผลที่ผู้ปกครองส่งบุตรหลานเรียนเสริมเพื่อเป็นการสันทนาการและการเสริมทักษะอื่นๆให้บุตรหลานมากที่สุด ส่วนเหตุผลที่ผู้ปกครองไม่ส่งบุตรหลานเรียนเสริมเพราะผู้ปกครองมีความพร้อมในการสอนบุตรหลานด้วยตัวเองมากที่สุด 3) วิชาที่เรียนเสริมมีความสัมพันธ์กับรายได้รวมของครอบครัว การศึกษา อาชีพ อายุของผู้ปกครอง และประเภทโรงเรียนที่นักเรียนเรียน จำนวนชั่วโมงที่เรียนและค่าใช้จ่ายที่เรียนเสริมต่อเดือน พบว่า ผู้ปกครองนักเรียนที่เรียนโรงเรียนมีชื่อเสียง มีระดับการศึกษาและระดับรายได้รวมของครอบครัวต่อเดือนสูงกว่าจะส่งบุตรหลานเรียนเสริมมากกว่าผู้ปกครองที่มีภูมิหลังต่ำกว่า ด้านเหตุผลในการเรียนเสริม พบว่า ด้านสันทนาการ และการเสริมทักษะอื่นๆ ไม่พบความแตกต่างกันตามภูมิหลัง แต่ระดับเหตุผลการเรียนเสริมด้านการเตรียมความพร้อมก่อนเรียน ด้านการพัฒนาการเรียนในห้องเรียน ด้านปัญหาหลักสูตรและการจัดการเรียนการสอน ด้านการเตรียมตัวสอบเข้าศึกษาต่อ ด้านความไม่พร้อมของผู้ปกครอง และด้านความเชื่อและค่านิยมของผู้ปกครอง แตกต่างกันตามระดับการศึกษาของมารดาและระดับรายได้รวมของครอบครัวต่อเดือน และประเภทโรงเรียน อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 The purposes of this study were 1) to study characteristics of out-of-school classes for preschool student in Bangkok : subjects, hours per week, type of and expense per month on out-of-school classes 2) to study reason for out-of-school classes and no study 3) to compare characteristics and reason for out-of-school classes with difference backgrounds 4) to study impact from out-of-school classes. The study had 2 phase. The qualitative study (1st phase), featured sample groups of 15 parents who send student study out-of-school classes and 10 parents who didn’t send student study out-of-school classes using interviews. The quantitative study (2nd phase), had a sample group of 594 parents from 14 schools (both famous and normal school) in Bangkok. The research instrument was a questionnaire. Data was analyzed by descriptive statistics, Chi-square and ANOVA . The research finding are 1) Preschool student learnt both academic and recreation subjects, 6.57 hours per week and 4117.56 baht per months to study out-of-school classes. Most of student study out-of-school classes at tutoring institutions with more than 5 persons class size. 2) The most reason of out-of-school classes was for recreation and enhanced variety skills and reason of no out-of-school classes was parents readiness. 3) The subjects of out-of-school classes was correlated with household income, parents’ education occupation and age, type of school. Household income, mother’s education and types of school was correlated out-of-school hours and expenditure so student who came from higher backgrounds pay more than the lower. Reason for out-of-school classes, founded difference reason level in Preparation before study, Improve achievement in school classes, Curriculums and teacher’s class management problems, Preparation for Prathom 1 examination, Parents’ unreadiness, Belief and values; founded that parents from lower household incomes, lower mom education and parents from normal school had higher rating than others. There was no founded differenced in recreation and enhanced variety skills reason.